2004
DOI: 10.1080/09637480410001725166
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic determination of organochlorine pesticides in cow milk

Abstract: A gas chromatographic method of use in determining the following organochlorine pesticides in cow milk has been adapted and validated: alpha-hexachlorocyclohexane (alpha-HCH), beta-HCH, lindane, delta-HCH, hexachlorobenzene, aldrin, heptachlor, heptachlor epoxide, mirex, 2,4-dichlorodiphenyltrichloroethane (2,4-DDT), 4,4-DDT, 2,4-dichlorodiphenyldichloroethane (2,4-DDD), 4,4-DDD, 2,4-dichlorodiphenylethane (2,4-DDE) and 4,4-DDE. The method studied consists of three steps: the extraction of fat by centrifugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…As such, they are consistent with those of Ganmaa et al's study where a mixture denoted ''artificial milk'' was used to mimic commercial milk [21]. Although protein, fat, and carbohydrate were present in this artificial milk at typical levels, the concentrations of minerals and contaminants were significantly different from those of real milk [10,22]. The main improvement of the study reported here is the use of traditional milk.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As such, they are consistent with those of Ganmaa et al's study where a mixture denoted ''artificial milk'' was used to mimic commercial milk [21]. Although protein, fat, and carbohydrate were present in this artificial milk at typical levels, the concentrations of minerals and contaminants were significantly different from those of real milk [10,22]. The main improvement of the study reported here is the use of traditional milk.…”
Section: Discussionsupporting
confidence: 79%
“…Most studies on milk have identified beneficial effects, such as the prevention of osteoporosis and the promotion of growth and development. However, milk also contains organochlorine pesticides and endogenetic estrogens, which are classified as EDCs [10]. Forty years ago, Armstrong and Doll reported an association between the intake of milk-based products and increased breast cancer mortality [11].…”
Section: Introductionmentioning
confidence: 99%